Water and Space in Literature and Cultures: Water Concepts in an Intercultural Comparison / Wasser als Raum in Literatur und Kultur: Wasserkonzepte im interkulturellen Vergleich - Feyrer, Cornelia (Kalbotyra, 2008)
The aim of the present article is to provide a certain transparency of concepts of water and space in patterns of thinking and orientation related to these concepts in literature and cultures. Working on examples taken from a literary text, the relevance of water and space in language and culture is described in this contribution. In this context the focus – seen from the point of view of translation – is placed on the universal relevance and the cultural determination as well as on the individually and supra-individually determined manifestation of water concepts and thinking patterns related to these concepts in cultures, culture comparison and language and culture transfer within the framework of the act of translation.